2018
DOI: 10.1371/journal.pone.0194225
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of protein biomarkers and network analysis unveils deregulated regulatory circuits in Duchenne muscular dystrophy

Abstract: Although the genetic basis of Duchenne muscular dystrophy has been known for almost thirty years, the cellular and molecular mechanisms characterizing the disease are not completely understood and an efficacious treatment remains to be developed. In this study we analyzed proteomics data obtained with the SomaLogic technology from blood serum of a cohort of patients and matched healthy subjects. We developed a workflow based on biomarker identification and network-based pathway analysis that allowed us to desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…The use of whole-genome expression data has been extensively used for the identification of novel pathogenic pathways and therapeutic targets in several pathologies including, immunoinflammatory/autoimmune diseases [26,27,28,29,30] and cancer [31,32,33,34,35], and have allowed identification of novel cellular and molecular targets [36,37]. Gene regulatory networks and pathway analysis may help the development of new therapies aimed at increasing muscle protection/regeneration, and some of them have already proven their effectiveness, also in DMD [38].…”
Section: Discussionmentioning
confidence: 99%
“…The use of whole-genome expression data has been extensively used for the identification of novel pathogenic pathways and therapeutic targets in several pathologies including, immunoinflammatory/autoimmune diseases [26,27,28,29,30] and cancer [31,32,33,34,35], and have allowed identification of novel cellular and molecular targets [36,37]. Gene regulatory networks and pathway analysis may help the development of new therapies aimed at increasing muscle protection/regeneration, and some of them have already proven their effectiveness, also in DMD [38].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, IL-1 ra and fractalkine both showed marked changes in protein levels; however, the patterns were complex bi-phasic responses. Such time-dependent changes in protein levels can still provide utility as biomarkers of disease progression or drug response, but should probably not be interpreted individually, but as part of a panel of other biomarkers to provide insight into the nature of the biological processes that are active at different times ( Parolo et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, extensive proteomic, RNA and metabolite analyses have been carried out in animal models and patients, as discussed in a number of excellent reviews on potential biomarkers for muscle, blood and urine (Aartsma-Rus et al, 2018; Aartsma-Rus and Spitali, 2015;Dowling et al, 2019;Hathout et al, 2014Hathout et al, , 2016Lourbakos et al, 2017;Parolo et al, 2018;Szigyarto and Spitali, 2018;Thangarajh et al, 2019). A large-scale proteomic approach to identify serum biomarkers associated with pathophysiological change over time (Spitali et al, 2018) concluded that ∼33 proteins were bona fide biomarkers as they were able to discriminate between DMD patients and healthy controls in all cohorts, with a concordant directional change towards either a consistent increase or decrease in patients.…”
Section: Overview Of Molecular Biomarkers Especially For Myonecrosismentioning
confidence: 99%